Professional sales management - Anderson, Rolph E. (Dame, 1999)
This book is divided into six parts: Overview of personal selling and sales management; Planning and organizing the sales force; Developing the sales force; Directing the sales force; Controlling and evaluating the sales force; and The environment for personal selling and sales management.